2015
DOI: 10.1515/squa-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Transformation of the Vegetation in the Immediate Vicinity of the Settlement Complex at Poganowo (Mrągowo Lakeland, Ne Poland)

Abstract: Ab stractThe re sults of pol len, non-pol len palynomorph and microcharcoal par ti cle anal y ses of de pos its from a small pond in north east ern Po land are pre sented. The study fo cused on hu man-in duced veg e ta tion changes that oc curred in a close vi cin ity of the set tle ment com plex at Poganowo dur ing the Mid dle Ages (ca 10 th -16 th cen tu ries). We dis tin guished three phases of hu man im pact. First and third phases cor re spond to in ten si fied set tle ment ac tiv ity. The sec ond phase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 33 publications
(44 reference statements)
0
2
0
1
Order By: Relevance
“…In addition, if oak woods were used as pastures, such management most probably led to subsequent changes in woodland composition and structure, which were connected with the prevention of forest succession. The issue of the significant spread of Quercus in the area situated close to the investigated sites was recently discussed by Szal et al (2015). These authors suppose that the observed changes in species composition, mainly the dominance of Quercus , developed under the substantial influence of human activity in the medieval period and to some extent were associated with moderate livestock grazing in woodland.…”
Section: Responses Of Selected Trees On Anthropressure and Climate Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, if oak woods were used as pastures, such management most probably led to subsequent changes in woodland composition and structure, which were connected with the prevention of forest succession. The issue of the significant spread of Quercus in the area situated close to the investigated sites was recently discussed by Szal et al (2015). These authors suppose that the observed changes in species composition, mainly the dominance of Quercus , developed under the substantial influence of human activity in the medieval period and to some extent were associated with moderate livestock grazing in woodland.…”
Section: Responses Of Selected Trees On Anthropressure and Climate Changesmentioning
confidence: 99%
“…Moreover, a significant spread of Quercus was accompanied by an increase in spores of coprophilous and parasitic fungi. Szal et al (2015) considered that grazing animals caused damage to the roots and trunks of oak trees, triggering infections with Kretzschmaria deusta . Also, in our record, significant values of Quercus and Carpinus were accompanied by an increase in the abundance of Kretzschmaria deusta and coprophilous fungi (Figures 3 and 4) and might be connected with woodland pasturing practice on the regional scale.…”
Section: Responses Of Selected Trees On Anthropressure and Climate Changesmentioning
confidence: 99%
“…2002;Cugny i in. 2010;Mazurkiewicz-Zapałowicz, Okuniewska-Nowaczyk 2015;Szal et al 2015;Revelles i in. 2016), a także ocenie zmian paleohydrologicznych (van geel i in.…”
unclassified